POLA RESISTENSI ANTIBIOTIK TERHADAP ISOLAT BAKTERI SPUTUM PENDERITA TERSANGKA INFEKSI SALURAN NAFAS BAWAH - Kumala, Shirly; Pasanema, Dimas A. M.; Mardiastuti, . (Jurnal Farmasi Indonesia, 2010)
Lower respiratory tract infection (LRTI) was one type of lung infection that is commonly suffered by the indonesion society including â??in patientsâ? in hospital ward.Â The percentage of lung infection case was found to be 60-80% of all case of lung related disease while the rest (20-40%) were classified as non-infectious lung disease.Â Fast and accurate diagnosis followed by correct choice of antibiotics based on antibiotic resistance test would certainly help to establish accurate diagnosis and treatment. Studies were carried out in clinical microbiology laboratory in the Faculty of Medicine of University of Indonesia.Â A total of 124 specimens were used in the study, contained sputtam excreted by patients diagnosed with lower respiratory tract infectious disease. Isolation and identification procedure was performed according to the Laboratory standard operational procedure (SOP).Â Antibiotic resistance test was performed using â??CAKRAMâ? diffusion techniques according to CLSI which is abbreviated as Clinical and Laboratory Standards Institute. 76 bacterial isolates were successfully isolated and identified.Â Most of the bacteria found were identified as Klebsiella Pneumoniae and they were Erithromycin sensitive and Ticarsilin resistant (75.9%). Â ABSTRAK Infeksi Saluran Nafas Bawah (ISNB) merupakan penyakit infeksi paru yang paling sering ditemukan di masyarakat maupun yang dirawat di Rumah Sakit, dan masih merupakan masalah kesehatan utama di seluruh dunia. Penyakit infeksi paru berkisar 60-80% dari seluruh penyakit paru, sedangkan sisanya (20-40%) merupakan penyakit non infeksi. Penentuan diagnosis secara cepat dan tepat serta pemilihan antibiotik berdasarkan uji resistensi akan sangat membantu dalam petanalaksanaan dan terapi. Penelitian dilakukan di Laboratorium Mikrobiologi Klinik Fakultas Kedokteran Universitas Indonesia, Jakarta. Spesimen yang digunakan berupa sputum penderita tersangka infeksi saluran nafas bawah, jumlah sampel 124. Isolasi dan identifikasi dilakukan sesuai standard operasional laboratorium, uji resistensi menggunakan difusi cakram menurut CLSI. Dari hasil isolasi diperoleh 76 isolat bakteri, yang terbanyakÂ adalah Klebsiella pneumoniae yang sangat sensitif terhadap Eritromisin dan resisten terhadap Tikarsilin (75,9%)